FROM DAWN TILL DUSK - AND BACK? MILORAD PAVIĆ IN DAILY AND ACADEMIC LITERARY CRITICISM OF THE GERMAN-SPEAKING COUNTRIES (Philological Studies, 2019)
The paper examines the reception of works by the Serbian writer Milorad Pavić in the German-speaking countries. Based on the theoretical approaches of the reception theory as they are formulated mainly by Hans Robert Jauss and Wolfgang Iser, it is the goal of this paper to analyze the critical reception of Pavić’s novels in the German newspaper or daily criticism, on the one hand, and within the academic research (literary science), on the other hand. Considering aesthetic, social and political aspects of the reception, the paper aims to show and explain the causes of a paradox development that went on as a transition from initial unanimous recognition of the writer to his moral stigmatization and expulsion from the literary map of the German-speaking countries
Keywords: Milorad Pavić, reception, reception theory, German speaking-countries, daily criticism, academic research (literary science), political context